(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The main purpose of the present study is to estimate the influence of the seasonality factor on the rate of unemployment in Bulgaria by comparing it with the European Union including its current 28 members. The dynamics and seasonal fluctuations in the rate of unemployment in Bulgaria have been studied by means of statistical models. The conclusion reached is that the seasonality factor exerts a greater influence on the rate and dynamics of unemployment in Bulgaria in comparison with the EU economy as a whole.